Optimalisasi Motivasi dan Pelatihan Kerja Dalam Meningkatkan Kinerja Karyawan Pada Perusahaan - Harmen, Hilma; Syahreza, Dina Sarah; Nuraina, Azra Lena; Pratiwi, Dian Maulina; Manurung, Indah Syahpitri; Manalu, Lija Tanjung; Warasati, Rina Kartika; Sikumbang, Riska Zunaidah (Peneliti.net, 2024)
This study aims to explore and synthesize findings from various previous studies related to optimizing work motivation and training in improving employee performance in companies. A literature review was conducted by analyzing 15 relevant research articles using a qualitative approach. The review results indicate that work motivation is influenced by intrinsic factors such as achievement, recognition, the work itself, as well as extrinsic factors such as administration, policies, salary, and working conditions. Some motivation theories discussed include Maslow's hierarchy of needs theory, Herzberg's two-factor theory, and contemporary motivation theories. Meanwhile, the types of job training identified include on-the-job training, off-the-job training, technical & technology training, as well as problem-solving and interpersonal skills training. Job training has been shown to have a positive influence in increasing employees' knowledge, skills and performance.